The Impact of Oil Exports on Imports of Agricultural Machinery and Equipment - Sugra Ingilab Humbatova; Galib Bahram Hajiyev; Leyla Zakir Aliyeva; Natig Gadim‒Oglu Hajiev (International Journal of Energy Economics and Policy, 2023)
The influence of the main export product on the main import product is the focus of any country. In this regard, since oil and oil products are the main export commodity of Azerbaijan, their impact on the import of machinery and equipment necessary for the development of the agricultural and agro −processing industries, which are the main imported products, was chosen as the subject of study. The purpose of the article was to assess the impact of the export of oil and oil products on the import of machinery and equipment necessary for the development of the agricultural sector and the agro −processing industry. The study used data for the period from 1999 to 2020. ARDL and ECM methods were applied and compared with FMOLS, DOLS and CCR as a validation. During the study, 9 hypotheses were proposed. All hypotheses have been proven to some extent. The results of the study show that, like all industries, the agricultural sector depends on the oil factor. Thus, the export of oil to the republic has a positive effect on imports and, of course, on the imports of many machineries and equipment necessary for the development of the agricultural sector, especially agricultural machinery for tillage and harvesting, equipment for the food industry and equipment for processing agricultural products. The overall result of the research was a recommendation to further acceleration of work aimed at diversifying the economy and developing the non −oil sector, similar to the results of other similar studies (researches investigating resource −exporting economies).